SUN-698 Management of Hyperglycemia in an Adult Patient with Glycogen Storage Disease Type 1b - Mikhael, Alexandra (J Endocr Soc, 2020)
Background: Glycogen storage disease type 1b (GSD1b) is caused by a deficiency of glucose 6 phosphatase leading to glycogen deposition. The hallmark findings of GSD1b are hypoglycemia and lactic acidosis. GSD1b can be associated with hepatomegaly, hypertriglyceridemia, hematologic abnormalities, hypothyroidism, inflammatory bowel disease, proteinuria, and hypoglycemic seizures. Main stay of therapy is to avoid fasting and to ingest frequent feeds high in complex CHO. Raw cornstarch (CS) has been used for the treatment of hypoglycemia in GSD1b since the early 1980s. CS is digested slowly, providing a steady release of glucose allowing for more stable glucose levels over a longer period of time as compared with other sources of CHO. Adults may require more CS to maintain BG >70 mg/dL and lactate <2mmol/L during the night. We report a case of an adult patient with GSD1b admitted with inability to tolerate oral intake and found to have persistent hyperglycemia on admission requiring insulin therapy. Clinical Case: A 31 year old female with a history of GSD1b complicated by hypoglycemia, Crohn’s disease, chronic pancreatitis and neutropenia was admitted for abdominal pain, emesis and inability to tolerate CS. She was made NPO and was started on a dextrose drip to avoid hypoglycemia and hyperlactatemia. The rate of dextrose infusion was adjusted to maintain lactate levels <2 mmol/L. She developed persistent hyperglycemia with glucose values of 250–350 mg/dL. Laboratory evaluation revealed an HbA1c of 7.6% (reference [ref] 4.3–5.6%), C-peptide of 1.3 ng/mL (ref 0.8–3.9 ng/mL), lactate of 2.3–3.1 mmol/L (ref 0.5–2.2 mmol/L). BHB levels were normal (WNL). Anti-GAD, insulin and islet cell antibodies were negative. The main goal was to avoid hypoglycemia while keeping ketone and lactate levels WNL. The decision was made to start a regular insulin infusion at a constant rate of 1 u/hr to keep BG <180 mg/dL while on the dextrose infusion with close monitoring of lactate and BHB. Insulin and dextrose drip rates were adjusted based on BG. The ultimate goal was to determine total daily insulin requirements while ingesting her home CS doses and to transition to long acting insulin. Short acting insulin boluses were not used given risk of hypoglycemia. The patient’s unpredictable tolerance to CS made determining a fixed insulin dose challenging. She eventually managed to tolerate CS and was transitioned to 10 units of insulin Detemir twice daily. She was discharged with plans to get a CGM and a ketone meter. BG readings at home were between 140–170 mg/dL. Conclusion: We report a rare case of GSD1b and diabetes. The pathogenesis may be related to effects of chronic pancreatitis or metabolic syndrome. Treatment of hyperglycemia in patients with GSD1b is challenging given the heightened risk of fasting hypoglycemia. Treatment options are limited, and there are no data regarding the safe use of insulin in this patient population.